Colonization of leaf litter of two aquatic macrophytes, Mayaca fluviatilis Aublet and Salvinia auriculata Aublet by aquatic macroinvertebrates in a tropical reservoir - Fabio Laurindo da Silva (Ambiente & Água - An Interdisciplinary Journal of Applied Science, 2011)
Decomposition and colonization of S. auriculata and M. fluviatilis by macroinvertebrates were analyzed during 40 days to determine whether differences existed on colonization by aquatic macroinvertebrates of two macrophytes with distinct habits (submerged versus fluctuant). Leaf litter of S. auriculata and M. fluviatilis were incubated in 24 litter bags (12 of each species), in a small reservoir surrounded by a cerrado fragment with low level of anthropic impact. After 10, 20, 30 and 40 days, the litter bags were removed and aquatic macroinvertebrates community was analyzed. Two hundred twenty macroinvertebrates were associated with S. auriculata and 261 were associated with M. fluviatilis, identified in 24 taxa. Both macrophyte species were colonized mainly by macroinvertebrate predators. Ablabesmyia with predator and collector food mechanisms was present in all sampling. The data showed an expressive increase of abundance during the process of decomposition and a decrease at the end of the experiment, in both macrophytes. Cluster analysis permitted inference that the colonization of the leaf liter by macroinvertebrates was determinated by incubation time of leaf litter not by the habit of macrophytes (submerged or fluctuant).